Urban Consumer Behavior On Buying Multi-Products On Shopee Using Technology Acceptance Model (TAM) - Michael Christian; Halim Agung (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2020)
People who live in urban areas can be explained as social groups that are sociologically in the middle class, have a productive life, and are part of social change. Shopee as one of the marketplaces in Indonesia always needs to consider the factor of technology usage that allows users to make purchases with a variety of products (multi-product) available. This study aims to analyze the behavior of using Urban Consumer Behavior with the Technology Acceptance Model (TAM) approach. Data analysis using SMART PLS 3.0 involving 163 samples in Jakarta with survey-questionnaire as a method of data collection. The results of this study explain that two hypotheses were accepted and two more hypotheses were rejected. In this case, Shopee's website/app usage behavior is influenced by the Ease of Use Factor. Furthermore the Benefit factor is influenced by the Ease of Use factor. On the other hand, usage is not influenced by usage behavior. Then the use is not influenced by the expediency factor. TAM as a classic model in explaining technology adoption in aspects of daily life is still needed to gain more understanding, especially on the characteristics of various or different samples.